Discovery and development of an oral analgesic targeting the α2B adrenoceptor - Masayasu Toyomoto; Takashi Kurihara; Takayuki Nakagawa; Asuka Inoue; Ryo Kimura; Isao Kii; Teruo Sawada; Takashi Ogihara; Kazuki Nagayasu; Takayuki Kishi; Hiroshi Onogi; Dohyun Im; et al. (Proceedings of the National Academy of Sciences, 2025)
Noradrenaline is a major monoaminergic neurotransmitter involved in pain modulation through an α2A-adrenergic receptor. Hence, α2-adrenergic agonists such as clonidine and dexmedetomidine exhibit analgesic and opioid-sparing effects. However, their use is restricted to hospital settings due to potential risks of acute hypertension/hypotension and bradycardia. Here, we report that ( Z )-1-(3-ethyl-5-fluorobenzo[ d ] thiazol-2(3 H )-ylidene)propan-2-one [adrenergic inducer of analgesia (ADRIANA)], a newly identified α2B subtype-specific antagonist, specifically promotes noradrenaline release in the murine spinal dorsal horn and produces analgesic effects by stimulating the α2A-dependent pain inhibitory pathway. Orally administered ADRIANA has potent analgesic effects in several nociceptive pain models of mice and nonhuman primates without cardiovascular effects. Mice with genetic loss of the α2B adrenoceptor showed normal responses to mechanical pain, but the analgesic effect of ADRIANA was not significantly detected. These findings reveal that the α2B adrenoceptor is a promising target for nonopioid analgesics through the activation of the α2A-dependent descending pathway.